Cosmetic Education Regarding the Making and Use of Hair Serum in Teenagers to Young Adults - Putriana Rachmawati; Meyliana Lukman; Evadia Nathalie; Angeline Jowi; Jocelyn Viony Lee (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Indonesia is a relatively large market for the cosmetics industry in the hair care category. Teenagers and young adults are among the dominant segments in cosmetic consumption. Hair and scalp problems often experienced are hair loss and unhealthy hair structure. This problem can be overcome with hair serum. This dosage form is attractive because it can be purchased freely and is quite promising due to its high active substance content. Various types of hair serums are available on the market so that they can be adjusted based on user preferences. The high level of public consumption of hair serum needs to be balanced with education regarding hair serum. The education process uses lecture and workshop methods related to identifying hair problems, the nutrition needed by hair, and the types and formulation of hair serum. The workshop was conducted directly by involving participants in producing the hair serum. The educational process was attended by 24 students aged 19-22 years, 21% coming from outside Atma Jaya and 79% from internal Atma Jaya. Gender includes 19% of men and the rest of women. The educational process increased the understanding of 92% of participants, with an average score from 5.9 to 9.75. As many as 96% of participants were very interested and stated that this workshop supported the theory that had been given to make it easier to understand.